Pulo ka satu : warisan sejarah awal persuratan Melayu Pulau Pinang - Jelani Harun, 1962- (Kuala Lumpur : Perpustakaan Negara Malaysia, 2013)
On history of Penang, Malaysia.
Includes bibliographical references : (page 283-301) and index.
In Malay.
Keywords: Malay literature -- History and criticism; Malay literature -- Pulau Pinang -- History; Pulau Pinang -- History